Factors Associated with Prolonged Observation Services Stays and the Impact of Long Stays on Patient Cost. (18th December 2013) - Hockenberry, Jason M.; Mutter, Ryan; Barrett, Marguerite; Parlato, Judy; Ross, Michael A.
<x xml:space="preserve">Abstract</x> Background Patients are treated using observation services (OS) when their care needs exceed standard outpatient care (i.e., clinic or emergency department) but do not qualify for admission. Medicare and other private payers seek to limit this care setting to 48 hours. Data Source/Study Setting Healthcare Cost and Utilization Project data from 10 states and data collected from two additional states for 2009. Study Design Bivariate analyses and hierarchical linear modeling were used to examine patient‐ and hospital‐level predictors of OS stays exceeding 48 (and 72) hours (prolonged OS). Hierarchical models were used to examine the additional cost associated with longer OS stays. Principal Findings Of the 696, 732 patient OS stays, 8.8 percent were for visits exceeding 48 hours. Having Medicaid or no insurance, a condition associated with no OS treatment protocol, and being discharged to skilled nursing were associated with having a prolonged OS stay. Among Medicare patients, the mean charge for OS stays was 10, 373. OS visits of 48–72 hours were associated with a 42 percent increase in costs; visits exceeding 72 hours were associated with a 61 percent increase in costs. Conclusion Patient cost sharing for most OS stays of less than 24 hours is lower than the Medicare inpatient deductible. However, prolonged OS stays potentially increase this cost sharing.